2005
DOI: 10.2511/rpsd.30.4.194
|View full text |Cite
|
Sign up to set email alerts
|

Stress Levels and Adaptability in Parents of Toddlers with and without Autism Spectrum Disorders

Abstract: The toddler years can be a particularly stressful time for all parents, however, parents of children with disabilities may experience additional sources of stress. Recent literature on early education for children with disabilities promotes inclusion with typical peers with increases in the availability of inclusive programs. However, little is known about early intervention inclusion programs and parental factors such as stress and adaptability. The current study expands the research for children with disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
209
2
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(241 citation statements)
references
References 42 publications
19
209
2
11
Order By: Relevance
“…Only in the last of the three areas fathers of children with autism obtained better results than fathers of children with Down syndrome. This result is consistent with the data obtained by Baker-Ericzen et al (2005), who found that fathers of children with autism perceive a negative impact of the child on family plans and increasing financial strain related to caregiving. By way of comparison, it is worth mentioning that the differences in stress profiles between mothers of children with autism and mothers of children with Down syndrome are much more profound and occur in seven areas: overprotection/ dependency, lack of social support, limits on family opportunity, physical incapatitation, lack of activities for index case social obtrusiveness and difficult personality characteristics (Pisula, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Only in the last of the three areas fathers of children with autism obtained better results than fathers of children with Down syndrome. This result is consistent with the data obtained by Baker-Ericzen et al (2005), who found that fathers of children with autism perceive a negative impact of the child on family plans and increasing financial strain related to caregiving. By way of comparison, it is worth mentioning that the differences in stress profiles between mothers of children with autism and mothers of children with Down syndrome are much more profound and occur in seven areas: overprotection/ dependency, lack of social support, limits on family opportunity, physical incapatitation, lack of activities for index case social obtrusiveness and difficult personality characteristics (Pisula, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Secondly, fathers of children with that disorder exhibit a high level of stress. Some 35% of them were found to have a significantly increased stress level directly associated with providing care for their child (Baker-Ericzen, Brookman-Frazee & Stahmer, 2005). Fathers of children with autism experience more stress than fathers of normally developing children (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a large percentage of Moderate impairment suggests that even in a community sample, many families of individuals with ASD experience significant distress (Baker-Ericzén et al, 2005). If data were collected from tertiary-level or crisis-related services, we might expect to find a higher percentage of Marked impairment (Weiss & Lunsky, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle, umudun engelli çocuk anne ve babaları için önemi oldukça büyük-tür. Bu ebeveynler çocuklarının müdahale programları ile korumak ve çocuklarının bakımına yönelik tüm gereksinimleri karşılamakla hükümlüdür (22). Lawoko ve Soares'in (25) konjenital kalp hastalıklı çocukların aileleri, diğer hastalıklı çocukların aileleri ve sağlıklı çocukların aileleri arasındaki stres ve umutsuzluk düzeyleri üzerine yapmış oldukları çalışmada, konjenital kalp hastalıklı çocukların ailelerinin, anneler daha fazla karamsar olmakla birlikte sağlıklı çocuk-ların ailelerine göre gelecek hakkında daha karamsar olduğunu saptamışlardır.…”
Section: Discussionunclassified